Influence of melatonin on reproductive performance and some blood parameters in rabbits - Akbulut, N.K.; Yıldız, I.; Yılmaz, M.T. (Polish Journal of Veterinary Sciences, 2026)
Melatonin not only regulates circadian rhythms in animals but also supports reproductive health through its potent antioxidant properties and immunomodulatory effects. In this study, the effects of exogenous melatonin administration on blood total antioxidant status (TAS), total oxidant status (TOS), Immunoglobulin G (IgG), Immunoglobulin M (IgM), and prolactin (PRL) concentrations, as well as on pregnancy rates and litter size, were investigated in rabbits. A total of 26 New Zealand rabbits were divided into two groups for the study. Melatonin implants were administered subcutaneously (SC) to group 1 (n=13) (MEL). Saline injections were administered to group 2 (n=13) (CON). Samples were collected from all rabbits before mating, on the 15th day of gestation and after parturition from the ear marginal vein and TAS, TOS, IgG, IgM, PRL concentrations and hemogram parameters were analyzed. Pregnancy rates were 77% and 92.3% in the CON and MEL groups, respectively, while litter sizes were 5.2 and 6 in the CON and MEL groups, respectively. TOS levels were found to be statistically lower (p<0.05) in the MEL group compared to the CON group just after parturition; however, there was no statistical difference between the groups in terms of TAS values at different times (p>0.05). IgG and IgM levels before mating and after parturition did not differ statistically significantly between the experimental groups when melatonin was administered. However, a statistically significant increase in the levels of both IgG and IgM was observed in the MEL group on day 15 of gestation. Exogenous melatonin administration did not alter reproductive parameters in New Zealand rabbits; however, it exhibited immunomodulatory effects on the 15th day of gestation and reduced oxidative stress after parturition.